Synthetic mRNA capping - Muttach, Fabian; Muthmann, Nils; Rentmeister, Andrea (Beilstein Journal of Organic Chemistry, 2017)
Eukaryotic mRNA with its 5′-cap is of central importance for the cell. Many studies involving mRNA require reliable preparation and modification of 5′-capped RNAs. Depending on the length of the desired capped RNA, chemical or enzymatic preparation – or a combination of both – can be advantageous. We review state-of-the art methods and give directions for choosing the appropriate approach. We also discuss the preparation and properties of mRNAs with non-natural caps providing novel features such as improved stability or enhanced translational efficiency.
Keywords: cap analogue; cap synthesis; click chemistry; enzymatic capping; methyltransferase; RNA